Abstentions in 2014 and 2019 Indonesian elections: Case study of pro-democracy activists - M Syaeful Anam; Gumilar Rusliwa Somantri (SIMULACRA: JURNAL SOSIOLOGI, 2020)
This article discusses how the dynamics of the abstentions phenomenon among pro-democracy activists in the 2014-2019 general election in Indonesia. While pro-democracy activists have increasingly chosen “struggle within”, there are still critical groups that have voted for abstentions in 2014-2019 general election. Charles Tilly’s concept of collective action and contentious politics is used in this study. This study uses a qualitative approach to the type of case study research. Researchers explore data through in-depth interviews as primary data and secondary data is extracted through library research. The analysis is carried out with the abstractive inductive logic. This research shows that abstentions are contentious collective actions. The abstentions movement was born from a network of pro-democracy activists who have been engaged in advocacy work. Abstentions carried out in protest against the authorities and the boycott of the election. The boycott choice is contentious politics.